Leadership decision making : an empirical test of the vroom and yetton model - Glube , R. H. R. (Cranfield University, 1978)
Despite common belief that greater worker participation in industry will increase productivity and worker job satisfaction, the empirical evidence has been most contradictory. Most theorists now belief that the degree of participation should depend on the particular problem facing the leader. For the practicing manager one -problem has been identification of the situation and subsequent selection of a appropriate decision method. One answer to this problem is the Vroom and Yetton Model which gives explicit directions to the leader as to how to identify the problem and select the appropriate decision method. The first objective of this research was to examine the extemal validity of that' model. A measure was also obtained of the leader's- preference for participation and this was compared to the dependent variables of ñrm productivity and worker satisfactionwith supervision. The sites chosen for the research were 47, owner-operated, small, nonuniorised, franchised rms, where the leader had the'-power and authority toreffect organisational outcomes. In these sites, there' was. relatively high control over the technology employed, tasks performed, number of levels of hierarchy, and the extemal environments. It was found that those leaders who had high agreement with the Vroom and Yetton model had higher productivity and workers with higher satisfaction with supervision than those leaderslow in agreement withe, the model. On the other hand, those leaders with a high preference for participation had workers with lower satisfaction with supervision than leaders with low preference for participation. No correlation was found between the leaders' preference for participation and the rms productivity. These findings give strong support for the Vroom and Yetton model, but raise the question of why some leaders should follow the model without having had any training in it.